2010
DOI: 10.1111/j.1751-2980.2009.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial study of microRNA expression profiles of colonic cancer without lymph node metastasis

Abstract: The miRNAs are differentially expressed between colonic tumor tissues and para-cancerous tissues. Many of these miRNAs are expected to participate in the process of multiple tumorigenesis. These miRNAs could play an important role in the carcinogenesis of colon. These results provide new insights in human colorectal cancer genesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 36 publications
10
129
1
2
Order By: Relevance
“…We identified 19 new miRNAs deregulated in CRC ( Table 1) that, to our knowledge, have never before been reported in cancer. We found deregulation of miR-1, miR-195, miR-143, miR-215, miR-31, miR-194, miR-30c, miR-133b, miR-192, miR-30b, miR-378*, miR-137, miR-133a, and miR-378 in CRC, which is consistent with earlier reports of miRNA expression in CRC (Michael et al, 2003;Bandres et al, 2006;Cummins et al, 2006;Volinia et al, 2006;Monzo et al, 2008;Arndt et al, 2009;Earle et al, 2010;Wang et al, 2010). Down-regulation of miR-378 in CRC compared with normal, observed in both our microarray and RT-PCR analysis, was also seen in a study by Wang et al (2010), who compared para-cancerous tissues and colorectal cancer samples.…”
Section: Mirna Profiling In Crc Versus Normal Colon Tissuesupporting
confidence: 82%
“…We identified 19 new miRNAs deregulated in CRC ( Table 1) that, to our knowledge, have never before been reported in cancer. We found deregulation of miR-1, miR-195, miR-143, miR-215, miR-31, miR-194, miR-30c, miR-133b, miR-192, miR-30b, miR-378*, miR-137, miR-133a, and miR-378 in CRC, which is consistent with earlier reports of miRNA expression in CRC (Michael et al, 2003;Bandres et al, 2006;Cummins et al, 2006;Volinia et al, 2006;Monzo et al, 2008;Arndt et al, 2009;Earle et al, 2010;Wang et al, 2010). Down-regulation of miR-378 in CRC compared with normal, observed in both our microarray and RT-PCR analysis, was also seen in a study by Wang et al (2010), who compared para-cancerous tissues and colorectal cancer samples.…”
Section: Mirna Profiling In Crc Versus Normal Colon Tissuesupporting
confidence: 82%
“…36 Particularly, the roles of miR-196a in cancer are elusive. Some reports suggest that miR-196a plays an oncogenic role in tumor development, 37,38 while others indicate that miR-196a may be a tumor suppressor. For instance, it was reported that the expression of miR-196a was dramatically decreased in melanoma cells when compared with healthy control melanocytes, and the low miR-196a expression in melanoma cells enhanced migratory potential of these melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The underlined genes miR-34a, miR-191 and miR-378 were reported to be up-regulated in some studies [71][72][73] and down-regulated in others [74][75][76] . healthy controls.…”
Section: Mirna Biomarkers In Bloodmentioning
confidence: 99%